Asteroidea of the southern tip of South America, including Namuncurá Marine Protected Area at Burdwood Bank and Tierra del Fuego Province, Argentina - Fraysse, Cintia Pamela; Calcagno, Javier Ángel; Pérez, Analía Fernanda (Polar Biology)
In benthic communities, echinoderms are dominant in terms of abundance and diversity, and Asteroidea play an important role in the structure of communities. In the present study, Asteroidea were sampled in the recently created Namuncurá Marine Protected Area (N MPA) at Burdwood Bank (which has an average of 50–200 m depth and is delimited by abrupt slopes), the surrounding shelf break and Tierra del Fuego Province, Argentina, at 24 stations at different depths and seabeds on board the oceanographic vessel ARA “Puerto Deseado.” A total of 32 Asteroidea species were identified. The bathymetric ranges were extended for two of them, and the geographic distribution was updated for seven of them, this being their first record in the N MPA. The N MPA showed higher asteroid richness than Tierra del Fuego Province and the surrounding shelf break. Moreover, this area presented species shared with Antarctica, which enhances the importance of the Malvinas Current (formed mainly by the contribution of Antarctic waters) in the larval dispersal of some species. On the other hand, a high percentage of the species found at the N MPA presented direct development with brooding females. The N MPA represents an important biodiversity hotspot. Thus, to contribute to the formulation of precise conservation strategies and enhance its protection, it is crucial to promote and continue the efforts to know more about the ecosystems at these latitudes. Fil: Fraysse, Cintia Pamela. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina. Universidad Maimónides. Área de Investigaciones Biomédicas y Biotecnológicas. Centro de Estudios Biomédicos, Biotecnológicos, Ambientales y de Diagnóstico; Argentina Fil: Calcagno, Javier Ángel. Universidad Maimónides. Área de Investigaciones Biomédicas y Biotecnológicas. Centro de Estudios Biomédicos, Biotecnológicos, Ambientales y de Diagnóstico; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina Fil: Pérez, Analía Fernanda. Universidad Maimónides. Área de ...